2021
DOI: 10.4103/ajps.ajps_90_20
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Polydioxanone (PDS) and Polyglactin (Vicryl) in Hypospadias Repair

Abstract: Background: Hypospadias is a fairly common problem, and it is the most common genital congenital anomaly. Objective: This study was carried out to compare polyglactin and polydioxanone in hypospadias repair by assessing the rate of complications, especially urethrocutaneous fistula (UCF) formation. Patients and Methods: This is a prospective observational cross-sectional hospital-based study carried out at the Department of Paediatric Surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…As there is still no definitive agreement on the suture material, many studies have attempted to compare the success and complications of surgery with different suture materials. In a study by Mohamed Ali Alaraby, which showed a lower rate of postoperative complications (34% vs. 10.9%) and better results when using PDS for hypospadias repair, polydioxanone proved to be better than Vicryl [ 11 ]. Another study compared PDS and Vicryl in hypospadias repair and showed that complications occurred more frequently with Vicryl sutures than with PDS sutures (15.1% vs. 5.3%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As there is still no definitive agreement on the suture material, many studies have attempted to compare the success and complications of surgery with different suture materials. In a study by Mohamed Ali Alaraby, which showed a lower rate of postoperative complications (34% vs. 10.9%) and better results when using PDS for hypospadias repair, polydioxanone proved to be better than Vicryl [ 11 ]. Another study compared PDS and Vicryl in hypospadias repair and showed that complications occurred more frequently with Vicryl sutures than with PDS sutures (15.1% vs. 5.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Different surgeons have different preferences as to when the optimal time for surgical correction of this anomaly is, but most agree that it is between the sixth and eighteenth month of life. This consensus has been reached by attempting to balance factors such as age-related genital dimensions and anesthetic risks, as well as the effects of toilet training and the potential psychological consequences of delaying surgery until an age when the child is genitally aware and remembers the procedure [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations